The Physical and Thermal Properties of Adobe Brick Containing Bagasse for Earth Construction - Lertwattanaruk, Pusit; Choksiriwanna, Jarunsri (International Journal of Building, Urban, Interior and Landscape Technology, 2011)
A form of natural architecture built with environmentally friendly materials, earth construction provides indoor protection from outside temperature conditions. In Thailand, adobe brick that contains rice husk is the most widely used material in earth construction. It is important to consider the strength and moisture absorption capacity of adobe brick. This research focuses on the feasibility of using agricultural by-products such as rice husk and bagasse in adobe brick mixtures with a percentage replacement of 0, 1, 2, 3 and 6% by weight of materials. The study explores the level at which replacing rice husk and bagasse in adobe brick effects optimal compressive strength, shrinkage, thermal conductivity, and moisture absorption. The results provide a guideline for producing adobe brick containing agricultural by-products with improved strength and lower moisture absorption. Adobe brick with performance improved in these ways will be beneficial for developing low-cost architecture for local people and for building hotels and recreation facilities for the tourism industry.